Valuing Ecosystem Diversity in South East Queensland: A Life Satisfaction Approach - Ambrey, Christopher; Fleming, Christopher (My University, 2013)
The valuation of complex environmental goods represents a considerable challenge for conventional non-market valuation techniques. The use of life satisfaction (or happiness) data has recently emerged as a new means of placing monetary values on non-market goods and services. This approach offers several advantages over more conventional techniques. This paper uses data from the Household, Income and Labour Dynamics in Australia survey along with Geographic Information Systems data to value ecosystem diversity in South East Queensland, Australia. It is found that, on average, a respondent has an implicit willingness-to-pay of approximately AUD$14 000 in household income per annum to obtain a one unit improvement in ecosystem diversity. This result confirms that the preservation, or improvement, of existing levels of ecosystem diversity is welfare enhancing. To our knowledge, this is the first paper to value ecosystem diversity using the life satisfaction approach.
Social Indicators Research
Keywords: Satisfaction -- Life; Lifestyle; Satisfaction; Life; Lifestyle